182k views
0 votes
Please ans this question pleaseee​

Please ans this question pleaseee​-example-1
User Maxthecat
by
5.2k points

1 Answer

2 votes

Answer:


{ \tt{ \tan {}^(4) \theta + { \sec }^(2) \theta }} \\ { \tt{ = ({ \tan }^(2) \theta ){}^(2) + { \sec }^(2) \theta }} \\ = { \tt{ {-(1 - { \sec }^(2) \theta) }^(2) + { \sec }^(2) \theta }} \\ { \tt{ = -(1 - 2 { \sec }^(2) \theta + { \sec }^(4) \theta) + { \sec}^(2) \theta}} \\ { \tt{ = -(1 - { \sec }^(2) \theta) + { \sec }^(4) \theta}} \\ { \tt{ = -{ \tan}^(2) \theta + { \sec }^(4) \theta }} \\ = { \tt{ { \sec}^(4) \theta - { \tan }^(2) \theta}} \\ { \bf{hence \: proved}}

User Adyusuf
by
6.5k points